2019
DOI: 10.1111/bjhp.12380
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in diurnal cortisol profiles in healthy adults: A meta‐analysis

Abstract: Purpose. Cortisol is a well-known biomarker of the physiological stress system; atypical cortisol patterns have been linked to many psychological and physiological illnesses. Previous studies have found vast health disparities among ethnic groups; however, studies examining the relationship between cortisol and ethnicity have found mixed results. This meta-analysis investigated whether there are differences in diurnal cortisol outcomes among ethnic groups, while considering the moderating roles of various indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Several explanations have been offered to explain this effect (Abell et al, 2016). First, certain ethnic groups are more likely to be exposed to biopsychosocial stressors (Boileau et al, 2019). Second, there are differences in the hair textures of different ethnic groups, and some textures may lead to more incorporation of cortisol into hair (Wosu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several explanations have been offered to explain this effect (Abell et al, 2016). First, certain ethnic groups are more likely to be exposed to biopsychosocial stressors (Boileau et al, 2019). Second, there are differences in the hair textures of different ethnic groups, and some textures may lead to more incorporation of cortisol into hair (Wosu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that previous studies were conducted in the Western parts of the world, some differences may have been due to our participants being from a Han Chinese population. Many studies revealed racial differences in cortisol levels [28][29][30][31] , one study also found that people of different ethnicity have different responses to psychological support under pressure [32] . All these suggest that cortisol and stress-related research may have ethnic differences.…”
Section: Cortisol Stress and Distress Intolerancementioning
confidence: 99%
“…Considering that previous studies were conducted in the Western parts of the world, some differences may have been due to our participants being from a Han Chinese population. Many studies revealed racial differences in cortisol levels [27][28][29][30] , one study also found that people of different ethnicity have different responses to psychological support under pressure [31] . All these suggest that cortisol and stress-related research may have ethnic differences.…”
Section: Cortisol Stress and Distress Intolerancementioning
confidence: 99%